Piko Hidro Archimedes Double Screw Turbine Berbahan Poly Vinyl Chloride Guna Menunjang Penerangan Pada Aquaculture - Aldiansyah; P Purnama; F L Ramadani; B Prastiyo; R S Tolo; A R Nasution (Cered Indonesia Institute, 2022)
The majority of coastal communities currently have income/jobs are fish cultivators, of work that has a reasonably high market prospect, due to the increasing demand for domestic and non-domestic markets. The fish farming sector in Indonesia has great potential to be developed. However, the obstacles experienced in the maintenance process caused a decrease in production yields, one of which was attacks from animals looking for prey due to the condition of the ponds that lacked lighting or lighting and the cost of electricity bills which was quite burdensome for partners. This program aims to design a pico hydro Archimedes double screw turbine made of polyvinyl chloride to support lighting in aquaculture.